THE USE OF CARTOON VIDEO IN TEACHING STUDENTS VOCABULARY - Muhammad Furqan; Muhammad Shabir (ENGLISH, 2021)
This paper aims to discuss vocabulary and cartoon video, and how to teach vocabulary by using cartoon video. Cartoons are designed not only to entertain children, but cartoons can be also used to teach and educate children. In order to find the relationship between cartoon and education, the writer writes a paper which the title is “The Use of Cartoon in Teaching Students Vocabulary”. It has a purpose to help children in learning English, more specifically it aims to improve English vocabulary for children whose age are between seven years old to fourteen years old.The method of the research is quantitative research in design experiment class and control class.The Reseacher could take conclusion that there was a significant between experiment class and control class, The mean of experiment class is greater than the mean of control class ( 77,25> 57,75). on the other hand, the test of hypothesis using t-test formula shows the value of t-test is greater than the value of the t-table. The value of t-test is 3,712 while the value of t-table on t-table in degree of freedom of 38 with level of significant of 0.01 is 2,42. The hypothesis is accepted.Based on the result of this study, it is accepted to be a good information for many teachers espesially English teachers. It is one solution to be used as appropiate method in teaching learning proses. It could be an alternative that could be used in teaching.